PUBISTYLUS THOTH. -AN INTERESTING NEW GENUS OF RUBIACEAE FROM ANDAMAN ISLANDS - K. THOTHATHRI (REINWARDTIA, 1966)
The tribe Alberteae of Rubiaceae consists of genera like Cremaspora Benth., Polysphaeria Hook, f., Belonophora Hook, f., Aulacocalyx Hook, f.,Rhabdostigma Hook, f., Alberta E. Mey., Nematostylis Hook f. and Octotropis Bedd. All the above mentioned genera are natives of Africa and Madagascar except Octotropis Bedd. which is a monotypic Indian genus, described from Travancore Hills. A new genus, Pubistylus Thoth. from the Andaman Islands is now added to this tribe. It is interesting to point out that there is no representative genus of this tribe in Malaysia whose flora has greatly influenced the Andaman and Nicobar Islands.